Diagnostic accuracy of an automated artificial intelligence derived right ventricular to left ventricular diameter ratio tool on CT pulmonary angiography to predict pulmonary hypertension at right heart catheterisation. Issue 7 (July 2022) - Charters, P.F.P.; Rossdale, J.; Brown, W.; Burnett, T.A.; Komber, H.M.E.I.; Thompson, C.; Robinson, G.; MacKenzie Ross, R.; Suntharalingam, J.; Rodrigues, J.C.L.
Abstract : Aim: To determine the diagnostic accuracy of an automated artificial intelligence derived right ventricle/left ventricle diameter ratio (RV/LV) computed tomography pulmonary angiography (CTPA) analysis tool to detect pulmonary hypertension (PH) in patients with suspected PH referred to a specialist centre. Materials and methods: The present study was a retrospective analysis of a prospectively maintained database of 202 consecutive patients with suspected PH, who underwent CTPA within 12 months of right heart catheterisation (RHC). Automated ventricular segmentation and RV/LV calculation (Imbio LLC, Minneapolis, MN, USA) was undertaken on the CTPA images. PH diagnosis was made using the RHC reference standard. Results: The automated RV/LV correlated more strongly with RHC metrics than main pulmonary artery (MPA) diameter and MPA to ascending aorta diameter ratio (MPA/AA) measured manually (mean pulmonary arterial pressure [mPAP] r=0.535, R 2  = 0.287 p <0.001; pulmonary vascular resistance [PVR] r=0.607, R 2  = 0.369 p <0.001). In the derivation cohort ( n= 100), the area under the receiver-operating curve for automated RV/LV discriminating PH was 0.752 (95% confidence interval [CI] 0.677–0.827, p <0.001). Using an optimised Youden's Index of ≥1.12 classified from derivation, automated RV/LV ratio analysis was more sensitive for the detection of PH with higher positive predictive value (PPV) when compared with manual MPA and MPA/AA in the validation cohort (n=102). Automated RV/LV compromise (1.12) and specific (1.335) thresholds were strongly predictive of mortality (log-rank 7.401, p =0.007 and log-rank 16.075, p <0.001 respectively). Conclusion: In suspected PH, automated RV/LV diameter thresholds have high sensitivity for PH, outperform manual MPA and MPA/AA and can predict survival. Highlights: Automated RV/LV analysis is feasible in real-world suspected pulmonary hypertension. Automated RV/LV thresholds perform favorably compared with manual metrics on CT in PH. Automated RV/LV analysis can predict survival in patients with suspected PH.